Cusp Forms in 𝑆𝟒(Γ𝟎(𝟒𝟕)) and the Number of Representations of Positive Integers by Some Direct Sum of Binary Quadratic Forms with Discriminant −𝟒𝟕 - Barış Kendirli (International Journal of Mathematics and Mathematical Sciences)
A basis of 𝑆4(Γ0(47)) is given and the formulas for the number of representations of positive integers by some direct sum of the quadratic forms 𝑥21+𝑥1𝑥2+12𝑥22, 2𝑥21±𝑥1𝑥2+6𝑥22, 3𝑥21±𝑥1𝑥2+4𝑥22 are determined.